THE EFFECT OF PERCEIVED WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AND ORGANIZATIONAL EFFECTIVENESS IN BAHIR DAR UNIVERSITY (Singaporean Journal of Business Economics and Management, 2020)
The study examined the effect of two constituents of work environment (i.e. physical and psycho-social on employees job performance and organizational effectiveness in Bahir Dar University. through stratified sampling technique, a sample of 213 employees was drawn from academic and administrative staffs. Statistical analysis was conducted by statistical package for social science (SPSS) version 20. The analyses revealed that participants who perceived their work environment as to be adequate and favorable scored comparatively higher on the measures of job performance and perceived organizational effectiveness. The two constituents of work environment were also found causing significant variance in employees' job behavior and their perception of organizational effectiveness. Regression analyses revealed that among the various components of work environment, working condition, safety and security, interpersonal relations, and rewards predominantly contribute to employees' job behavior and organizational effectiveness. The results also specified that psycho-social environment in work-place exert more impact on employees' job performance and organizational effectiveness than the physical environment does.